2022
DOI: 10.1111/bjet.13204
|View full text |Cite
|
Sign up to set email alerts
|

What influences student situational engagement in smart classrooms: Perception of the learning environment and students' motivation

Abstract: Situational engagement plays a critical role in promoting students' academic performance. In a smart classroom environment, this study collected longitudinal real‐time data for 105 college students at a university in central China to investigate the relationship among situational engagement, personal characteristics and learning environment perceptions. Hierarchical linear modelling showed that environmental perception and students' personal factors have different effects on situational engagement. Specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 78 publications
(143 reference statements)
2
23
0
Order By: Relevance
“…This study found that educational situation perception significantly correlated with students’ online learning engagement, thus verifying the previous research which highlighted the significance of educational situation perception in promoting students’ perception of online learning environments, sense of participation, learning satisfaction, and positive outcomes ( Saini and Goel, 2019 ; Zhao et al, 2014 ). The findings also confirmed previous researchers’ assertion that educational situation is an accurate representation of the existing state, evolution mechanism and interaction relationship of the entity factors such as human, machine, and environment under the real learning space–time condition, the function of which is to trigger the different dimensions of learning engagement ( Lu et al, 2022 ) and support the learning process ( Xie et al, 2019 ). As such, educational situation perception can help enhance students’ technology-enhanced learning experience and promote trust among group members, an important precondition for computer-supported collaborative learning ( Gerdes, 2010 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study found that educational situation perception significantly correlated with students’ online learning engagement, thus verifying the previous research which highlighted the significance of educational situation perception in promoting students’ perception of online learning environments, sense of participation, learning satisfaction, and positive outcomes ( Saini and Goel, 2019 ; Zhao et al, 2014 ). The findings also confirmed previous researchers’ assertion that educational situation is an accurate representation of the existing state, evolution mechanism and interaction relationship of the entity factors such as human, machine, and environment under the real learning space–time condition, the function of which is to trigger the different dimensions of learning engagement ( Lu et al, 2022 ) and support the learning process ( Xie et al, 2019 ). As such, educational situation perception can help enhance students’ technology-enhanced learning experience and promote trust among group members, an important precondition for computer-supported collaborative learning ( Gerdes, 2010 ).…”
Section: Discussionsupporting
confidence: 88%
“…Through accurate perception and integration analysis of educational situation in ubiquitous learning environments, precise, timely and actionable information was provided, helping students learn in a meaningful, relevant context ( Plass et al, 2015 ). Following on from this, Lu et al (2022) investigated the relationship among situational engagement, personal characteristics and learning environment perceptions oriented to intelligent learning environments, aiming to realize the dynamic optimization of intelligent learning space by using situational perception technology. On the whole, as education situation perception is the hot topic of the field of intelligent education, some applications of these models/theories are found in underpinning the studies examining the construction of the intelligent learning environment ( Aleven et al, 2017 ), the adaptive learning support service based on situational perception ( Bligh and Crook, 2017 ) and the modeling of learners’ learning behaviors based on situational perception ( De Corte, 2012 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has also demonstrated that students' motivation and learning engagement can be considerably boosted by building their relationship with their teachers (Reeve, 2012). When students are supported by their teachers, their motivation to learn is improved and they become more focused on classroom learning activities (Ryan and Patrick, 2001;Boulton et al, 2012;Lu et al, 2022). This may be related to the teacher expectation effect.…”
Section: The Mediating Effect Of Learning Motivationmentioning
confidence: 99%
“…Student engagement is associated with academic success and seems to foster wellbeing in school ( Upadyaya and Salmela-Aro, 2013 ; Lu et al, 2022 ). In past research it has been defined by the effort that is put in activities that are associated with positive learning outcomes ( Krause and Coates, 2008 ).…”
Section: Introductionmentioning
confidence: 99%